Description of Facilitator Andragogy Competence in Avocado Breeder Training at the West Sumatra Agricultural Training Center - Fifi Rahman Tusadiah; Jalius Jalius (Universitas Negeri Padang, 2021)
This study describes the andragogy competence of facilitators in the training of avocado breeders at the West Sumatra agricultural training center who are competent. This can be seen through the approach and encouragement made by the facilitator to the training participants in carrying out the training, then the facilitator also uses appropriate learning media and appropriate training methods. The objectives of this study are to (1) describe the Andragogy Competence of the Facilitator in understanding the learning community. (2) Describe the Andragogy Competence of the Facilitator in designing learning. (3) Describe the Andragogy Competence of the Facilitator in carrying out learning. (4) Describe the Andragogy Competence of the Facilitator in evaluating learning. This research is a research with a quantitative approach and the type of this research is descriptive. The population in this study were 30 people, the sampling technique was random sampling and taken as many as 50% or as many as 15 people. Techniques in collecting data using a questionnaire and data collection tools in the form of a list of statements. The data analysis technique uses the percentage formula. The results of this study indicate that: (1) Description of the andragogy competence of facilitators in avocado breeder training at the West Sumatra Agricultural Training Center. Judging from the sub-variable Understanding Learning Citizens, it is categorized as competent. (2) Description of facilitator's andragogy competence in avocado breeder training at the West Sumatra Agricultural Training Center. Judging from the sub-variables in designing learning, they are categorized as competent. (3) Description of facilitator's andragogy competence in avocado breeder training at the West Sumatra Agricultural Training Center. Judging from the sub-variables carrying out learning are categorized as competent. (4) Description of facilitator's andragogy competence in avocado breeder training at the West Sumatra Agricultural Training Center. Judging from the sub-variables, evaluating learning is categorized as competent. For further researchers to be able to use this thesis as a reference and to look for new findings so that they can increase the existing variables.